Starvation resistance in juvenile freshwater crayfish - Calvo, Natalia Soledad (2012)
Strong starvation resistance has been observed in larval decapods developing in freshwater where food appearance may be unpredictable or poor. The point-of-no-return (PNR) has often been utilized to quantify the vulnerability of a given species or developmental stage to starvation. Most studies of nutritional effects on decapods focus on marine species, while there is less information on freshwater species. We evaluated the effects of starvation on survival, growth, and hepatopancreas structure of both early (first free-living stage, JIII) and late (1 g, J1g) juveniles of Cherax quadricarinatus. The experiments consisted of treatments with increasing numbers of days without food followed by continuous feeding until Day 60 (experiment with JIII) or 90 (experiment with J1g). Regardless of body size, the time from the beginning of the experiment to first ecdysis increased with the length of the starvation period. Growth was affected by starvation in JIII, but it recovered after feeding, while growth could not be fully compensated during subsequent feeding in J1g. PNR values (means ± SD) were 8.7 ± 0.3 and 51.0 ± 1.5 d, corresponding to 125 and 220% of total stage duration, respectively. In conclusion, juvenile C. quadricarinatus are highly resistant to starvation compared to early stages of other decapods. Freshwater environments with unstable conditions of food availability may have selected for strong starvation resistance, i.e. low nutritional vulnerability. This feature gives this species potential importance for aquaculture and as an invader. © Inter-Research 2012.